Rethinking Tawhid and Tolerance: A Theological Study of Fethullah Gülen in the Context of Plural Societies - Muhammad Adress Prawira Negara, Adress; Rahmat, Hidayatullah (Tashwirul Afkar, 2024)
This study aims to reconstruct the concept of tawhid in the thought of Fethullah Gülen as a theological foundation for active tolerance in plural societies. The research is motivated by the rising tide of religion-based intolerance across various countries, including Indonesia, highlighting the need for an inclusive and transformative Islamic theology. The method employed is qualitative literature research with thematic analysis of Gülen’s key works, alongside scholarly literature on the twin tolerations theory and active tolerance. The main findings indicate that Gülen interprets tawhid relationally-that is, as an ethical principle linking spiritual connection with God to social responsibility towards fellow human beings. The concepts of love (mahabbah) and freedom of belief in Gülen’s thought are not only of spiritual value but also serve as the foundation for social praxis through education, interfaith dialogue, and cross-cultural service within the Hizmet Movement. The study concludes that Gülen’s thought constitutes a framework of Islamic public theology compatible with democracy and multiculturalism. The study’s original contribution lies in integrating a Sufi theological framework with modern political theories of tolerance, and in presenting a model of participatory Islamic theology applicable to inclusive social and educational policy.